Is cardiovascular risk factors prevention necessary from childhood? What do prospective studies show - A. A. Alexandrov; V. B. Rozanov; E. Yu. Zvolinskaya; Kh. S. Pugoeva (Кардиоваскулярная терапия и профилактика)
The analysis provided of prospective studies of dynamics of the main cardiovascular risk factors (RF) from childhood until adulthood. The importance of such study is posed by insufficient effectiveness of prevention programs in adult population. Many issues not solved on the development of scientifically based approaches to early prevention in childhood and adolescence: what does facilitate RF formation, and what age is the most vulnerable? What determines resistibility of the RF and their transformation to adult life? What is the risk grade for CVD development in adult age, of children and adolescents? If in general it is clear, what population aim should be fulfilled for early CVD prevention: policy making, increase of a school importance, food industry reorganization, physical culture and sport programs realization, — it is still not known, what does determine RF stabilization or their spontaneous normalization. Solution of this issue could improve risk groups determination for preventive procedures.